Horizontally aligned carbon nanotubes for interleukin-6 detection - Choo, Teck Kian (2015)
Biosensors are devices that can generate signals based on specific interactions between receptors and biomolecules. These signals can be converted into readable data to achieve qualitative and quantitative measurement of a particular analyte of interest. There are various types of biosensors currently available. In this report, a liquid gated Carbon Nanotube Field Effect Transistor (CNTFET) sensor based on horizontally aligned Single Walled Carbon Nanotube (SWCNT) is proposed for the detection of Interleukin-6 (IL-6), a pleiotropic cytokine responsible for a host of biological activities. The sensor operates by measuring the change in source drain current (ISD) upon interactions between Interleukin-6 molecules and the Interleukin-6 antibodies (IL-6R). The proposed sensing platform exhibits good sensitivity (limit of detection = 7.8 pg/mL), which is lower than the circulating levels found in human body. This can be attributed to the reduced tube to tube contact resistance and higher charge carrier mobility achieved by horizontally aligned SWCNT. Based on the results obtained, it can be concluded that the proposed CNTFET sensor platform is a promising platform for the detection of circulating Interleukin-6 levels and could play significant roles in areas of general healthcare and sports science.